Da economia agrário-industrial à tecnologia da informação e comunicação: Jaguariúna-SP sob o olhar CTS - Gomes, Geovane Ferreira (Universidade Federal de São Carlos, 2010)
This dissertation examines under the perspective of the STS field (Science, Technology and Society) the installation process of industries related to the branch of Information and Communication Technology (ICT) in the 1990s and 2000s, in Jaguariuna/SP. Among other issues, this work aims at identifying the factors that enabled the transition from an agriculture-based model to another focused on ICT, and at how this agrarian-industrial transition impacted socio-economic indicators in the municipality. It starts with the assumption that local policies, such as tax incentives, may even attract investments but are not able to build bonds and secure them in the new territories. It is not the companies and therefore their production models that fit in the new territories; these are molded in different scales to meet the companies interests. A descriptive-documentary methodology was adopted, a survey was performed on national databases, and it was consulted legislation on the subject, which enabled an quality-quantitative analysis of the results. The investigation indicates that the installation of ICT companies impacted positively the social indicators of the city; shows a significant but not dominant role of the local policies to attract such investments; as well as demonstrates the transitory nature of territorial ties and schedules an important debate about the real impact of local culture in these organizations modus operandi.
Keywords: Desenvolvimento social - ciência, tecnologia e sociedade; Tecnologia da informação e comunicação; Jaguariúna (SP); Jaguariúna; Information and Communication technology; STS Field (Science, Technology and Society); CIENCIAS SOCIAIS APLICADAS::ECONOMIA::ECONOMIA INDUSTRIAL::MUDANCA TECNOLOGICA